Prospek Pendidikan Islam - Niken Ristianah (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2019)
Education is very important in human life in the current era. However, in implementing education there are certainly a number of challenges both internal and external. This educational challenge consists of the problem of national unity, democratization of education, globalization, modernization, decentralization of education management, and the quality of education. Where Islamic Education that occurred in the past is different from Islamic education in the present. That is because the situation and conditions are also different problems faced. Especially if we imagine the future Islamic education. Therefore we must prepare Islamic education to be able to compete with other education in order to face a future that is full of challenges. Quality human resources are the answer to be able to face the challenges that exist.